B30 Investigating Hepatic Dysfunction In The Httq111/+ Mouse With A Perturbagen-based Primary Hepatocyte System. (17th September 2014) - Weston, R; Rodier, J; Coffey, S; Glickenhaus, A; Boros, LG; MacDonald, ME; Carroll, JB
Abstract : Background: We are interested in mapping and understanding phenotypes that precede the development of overt signs of Huntington's disease, in hopes of identifying pathways with the potential to be disease-modifying. Notably, the Huntington's disease mutation is associated with early metabolic alterations of unknown aetiology in both humans and various model systems. Our own data suggest that widespread metabolic alterations occur very early in B6. HttQ111/Q7 mice, which precisely recapitulate the genetics of human HD patients. Aims: We aim to understand which tissues reveal the earliest transcriptional and metabolic changes in the B6. HttQ111/Q7 mice. Methods: We are applying stable isotope-based dynamic metabolic profiling (SiDMAP) to cells and tissues to quantify metabolic flux, and RNA sequencing (RNASeq) to quantify transcript abundance. Results/outcome: In a cross-tissue metabolic flux study of 90-day-old mice using U13C-glucose as a stable tracer, we observe that the most robust metabolic changes are observed in the liver. Transcriptomic analysis of matched samples with RNASeq reveals that the liver has more genotype-sensitive transcripts at this stage than does the striatum, the most vulnerable tissue in HD. Based on these in vivo results, we hypothesise that very early changes in fatty acid synthesis, mobilisation and/or catabolism are occuring in the liver of HttQ111/+ mice. To study this hypothesis in more mechanistic detail, we have established a system of primary hepatocytes isolated from 90 day old mice fed one of 3 diets from weaning as a lipid-relevant perturbagen: high fat (65% kcal/fat), medium fat (45% kcal/fat) and normal chow (10% kcal/fat). We reason that examining phenotypes in HttQ111/Q7 cells at steady states may not be as informative as investigating their dynamic responses to chemically defined perturbations. Our phenotypic analysis in vitro includes quantifying metabolic flux using multiple flux tracers (1, 2–13C2-glucose and U13C-palmitate). We are also collecting transcriptomic data from matched samples using RNASeq, in hopes of identifying genotype-sensitive flux changes that are associated with coherent transcriptional alterations. Conclusions: We conclude that early transcriptional and metabolic flux changes occur in the livers of B6. HttQ111/Q7 mice.